1997
DOI: 10.1088/0268-1242/12/6/017
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of deep-level spectrum of irradiated silicon due to hydrogenation under wet chemical etching

Abstract: The effect of wet chemical etching in acid solutions on the energy spectrum of n-and p-type silicon crystals previously irradiated with high-energy electrons is studied by deep-level transient spectroscopy. It is observed that together with the well known radiation defects a number of novel deep-level centres appear near the etched surface. The depth profiles of the deep-level centres are investigated depending on the irradiation dose and the temperature of subsequent annealing. The novel centres observed are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 26 publications
8
29
0
1
Order By: Relevance
“…The fact that deuterium is less effectively captured by defects than H atoms was recently reported on silicon samples implanted with high fluences of H and D (> 10 16 cm -2 ) ions [13]. Presented spectra show similar features to those reported by other authors on electron-irradiated silicon subjected to wet chemical etching [3,7] or preceding treatment by hydrogen or deuterium [10] plasma. Lowering of three major peaks related to VO and V 2 centres is accompanied by appearance of two new levels P2 and P3 at E C -0.309 and E C -0.365 eV, respectively.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…The fact that deuterium is less effectively captured by defects than H atoms was recently reported on silicon samples implanted with high fluences of H and D (> 10 16 cm -2 ) ions [13]. Presented spectra show similar features to those reported by other authors on electron-irradiated silicon subjected to wet chemical etching [3,7] or preceding treatment by hydrogen or deuterium [10] plasma. Lowering of three major peaks related to VO and V 2 centres is accompanied by appearance of two new levels P2 and P3 at E C -0.309 and E C -0.365 eV, respectively.…”
Section: Methodssupporting
confidence: 86%
“…Levels E1-E3 appearing in both the FZ and CZ material after irradiation are connected with pure radiation defects [1,8,12]. Peak E1 arises from two defects complexes: vacancy-oxygen (VO) and substitutional carbon-interstitial carbon (C i -C s ) [7,8,12]; E2 is connected with the double acceptor (V 2 =/-) level of divacancy, and the vacancy-phosphorous (VP) pair and the single acceptor (V 2 -/0 ) level of divacancy [1,3,7,8,12] Detected after irradiation (E), plasma treatment (P) and annealing (A). contribute to the signal of the level E3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By means of DLTS, it is possible to follow the evolution of these phenomena, e.g., the transformation of VO to VOH. In the case of electron irradiation, the in-diffusing hydrogen faces a uniform defect distribution 51,53 and initially, the depth profile of the VOH centers formed shows a diffusion-like shape from the surface. At later annealing stages, while the hydrogen front advances into the bulk, passivation of the VOH centers occurs in the near-surface region and neutral VOH 2 centers form.…”
Section: B Vo Centermentioning
confidence: 99%
“…Recently, Feklisova and Yarykin [275] have suggested that the dependence of the defect concentration on depth might be used to identify the chemical composition of the defect. Assuming that multi-H defects are formed by diffusion of H from the surface, which is varying during the etching process, and successive capture of H by the defect, the authors argued that the concentration-depth dependence of a TM-H n defect, containing n H atoms, is…”
Section: Experimental Techniquesmentioning
confidence: 99%